2012
DOI: 10.1134/s036211971203005x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral frontal theta-waves in EEG of 7–8-year-old children with learning difficulties: Qualitative and quantitative analysis

Abstract: We analyzed EEG recorded in the rest condition (eye closed) in 22 children aged from 7 to 8 years old who experienced learning difficulties and whose EEG recordings were characterized by sporadic short term appearance of bilateral synchronous slow waves over the frontal and/or frontal and central corticesfrontal theta waves (FTW). The vector autoregressive modeling was used in order to assess the strength of directed cortico cortical functional connectivity pattern for FTW and for surrounding EEG. The comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Study [16] has shown that the VAR model can resolve the autospectrum of channel k for M channels (of electroencephalographic leads) into independent components where the detached summand reflects the off diagonal matrix V of the covariance matrix of autore gressive residuals, and function corresponds to the contribution of channel n to the autospectrum of channel k.…”
Section: X(f) = H(f)e(f) (11)mentioning
confidence: 99%
“…(15), , t) of the x(t) signal is con structed by the same principle as the Fourier transform but, in contrast to it, depends on two arguments: fre quency and time. As in the framework of frequency analysis, the cross spectrum is defined as = and the complex coherence func tion is defined as (16) Equation (16), similarly to the traditional coherence function (1), implies that the values in the terms of the fraction are exposed to preliminary statistical averag ing. Statistical connection may be assessed using the absolute value (16), as well as its real or imaginary parts.…”
Section: X(f) = H(f)e(f) (11)mentioning
confidence: 99%
See 2 more Smart Citations